Comprehensive studies on polyethylenimine filled polypropylene and its potential application in carbon dioxide sequestration. Issue 10 (23rd August 2019) - Patra, Pratim Kumar; Jaisingh, Aanchal; Goel, Vishal; Luthra, Priyanka; Kapur, Gurpreet Singh; Nebhani, Leena
Abstract : Polypropylene (PP) was blended with branched polyethylenimine (PEI) with the aim to prepare blends having CO2 adsorption property. The CO2 adsorption properties will be conferred due to the presence of variety of amine functionality in PEI. PEI contains primary, secondary as well as tertiary amine groups. Before testing CO2 adsorption, PP–PEI blends were characterized using variety of techniques, for example, differential scanning calorimetry, thermogravimetric analysis, dynamic mechanical analysis, scanning electron microscopy, and polarized light optical microscopy. In this work, we have studied in detail both compatibilized as well as noncompatibilized blends of PP and PEI. The compatibilization was achieved via addition of maleic anhydride grafted PP. Finally, all the compatibilized as well as noncompatibilized blends were studied for CO2 adsorption. The compatibilized blends showed better thermal, mechanical as well as CO2 adsorption properties as compared to the noncompatibilized blends. POLYM. ENG. SCI., 59:2092–2102, 2019. © 2019 Society of Plastics Engineers